1992
DOI: 10.1159/000126180
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressants Increase Glucocorticoid and Mineralocorticoid Receptor mRNA Expression in Rat Hippocampus in vivo

Abstract: Adrenal corticosteroids bind to hippocampal glucocorticoid (GR) and mineralocorticoid receptors (MR), thereby affecting neurochemical transmission leading to altered mood, behaviour and neuroendocrine control. Serotoninergic (5-HT) and noradrenergic projections innervate the hippocampus, interacting with corticosteroid-sensitive cells. We have previously demonstrated that lesions of 5-HT neurons reduce hippocampal GR and MR mRNA levels and now examine whether acute or chronic treatment with antidepressant drug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
85
3

Year Published

1994
1994
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 240 publications
(96 citation statements)
references
References 30 publications
8
85
3
Order By: Relevance
“…It is interesting that, in FVB/N controls, there were no effects of desipramine on GR expression in the cortex, and there was a tendency (although not significant) for a GR downregulation in the amygdala. Very few studies have examined the effects of tricyclic antidepressants on GR expression in these areas, and, consistent with our results, have found that GR is decreased (not significantly) in the amygdala (Peiffer et al, 1991b), and unchanged in the cortex (Seckl and Fink, 1992), in the presence of GR upregulation in the hippocampus (Peiffer et al, 1991b;Seckl and Fink, 1992). In contrast, one study in transgenic mice with decreased GR expression has found that desipramine increases GR expression in the cortex of these animals (Pepin et al, 1992).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…It is interesting that, in FVB/N controls, there were no effects of desipramine on GR expression in the cortex, and there was a tendency (although not significant) for a GR downregulation in the amygdala. Very few studies have examined the effects of tricyclic antidepressants on GR expression in these areas, and, consistent with our results, have found that GR is decreased (not significantly) in the amygdala (Peiffer et al, 1991b), and unchanged in the cortex (Seckl and Fink, 1992), in the presence of GR upregulation in the hippocampus (Peiffer et al, 1991b;Seckl and Fink, 1992). In contrast, one study in transgenic mice with decreased GR expression has found that desipramine increases GR expression in the cortex of these animals (Pepin et al, 1992).…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, in humans, we have shown that an increase in GR-mediated negative feedback is already present after as little as 4 days of antidepressant treatment (Pariante et al, 2004a). However, considering that the first paper describing this effect in cells was published in 1989 (Pepin et al, 1989), and the first papers in animals shortly afterward (Peiffer et al, 1991b;Seckl and Fink, 1992), it is perhaps surprising that we do not yet know how antidepressants increase GR expression and function. According to the classical model of antidepressant action, these drugs work by increasing the monoaminergic neurotransmission in the brain (Nemeroff and Owens, 2002), and in fact there is a direct cross talk between monoaminergic neurotransmission, glucocorticoid hormones, and corticosteroid receptors (Yau et al, 1997;Lai et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…In line with the finding of Brady et al (1992), the SSRI increased MR and GR mRNA levels in the hippocampus after 8 weeks, but not after 2 weeks, of drug treatment, indicating that differential regulatory mechanisms are operating to adjust limbic corticosteroid receptor number during antidepressant treatment. Similar antidepressant-induced increases of MR and GR mRNA expression have been reported in several in vitro and in vivo studies (Budziszewska et al, 1994;Pepin et al, 1989;Pfeiffer et al, 1991;Reul et al, 1993;Seckl and Fink, 1992). It has also been shown that chronic administration of lithium, which is known to augment clinical effects of medication in depressed patients, as well as prolonged application of electroconvulsive shock (ECS), regarded as a nondrug therapy of depression, elevate GR mRNA levels or the density of GR and MR in the rat hippocampus (Pfeiffer et al, 1991;Przegalinski et al, 1993).…”
Section: Discussionsupporting
confidence: 65%
“…Preclinical studies on the effects of the chronic administration of different antidepressants demonstrate that a decrease of the HPA-axis activity is a final common pathway of antidepressant effects, but that the different antidepressants unfold their specific pharmacological efficacy on varying HPA-axis levels and receptor subsystems. Tricyclic antidepressants as well as the SSRI fluoxetine are likely to increase either GR m-RNA or MR m-RNA expression in the hippocampus, depending on the type of drug (Barden et al, 1995;Brady et al, 1992;DeRijk et al, 2001;Holsboer and Barden, 1996;Jensen et al, 1999;Okugawa et al, 1999;Seckl and Fink, 1992). Owing to the increase of hippocampal MRs and GRs, they are thought to regain their balance re-establishing the inhibitory tone on the PVN in the hypothalamus.…”
Section: Discussionmentioning
confidence: 99%